Microeconomics : - McConnell, Campbell R. (McGraw-Hill/Irwin, 2005)
This is the leading Principles of Microeconomics textbook. It continues to be innovative while teaching students in a clear, unbiased way. The 18th edition builds upon the tradition of leadership by sticking to 3 main goals: help the beginning student master the principles essential for understanding the economizing problem, specific economic issues, and the policy alternatives; help the student understand and apply the economic perspective and reason accurately and objectively about economic matters; and, promote a lasting student interest in economics and the economy.